(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background of the study: - While the trusted sources of Medical Council of India suggests that India is one of the largest exporter of generic medicine that constitutes almost 22% of the total export of the country, still a mass scale inaccessibility persists in the use of the generic drugs, in India itself. Being the replica of the branded drugs, there is a gap in-between availability and accessibility of these drugs. The scheme ‘Pradhan Mantri Bharatiya Janausadhi Pariyojana (PMBJP)’, is a central-flagship programme in order to reduce the out-of-pocket expenditure in medicines. However, the market structure shows that there are certain anomalies involved in it. This is a virtual gap in the real health market. The medicines are exported on a large scale to various developed nations but the country’s scenario is way different. Since physicians predominately prescribe drugs in medical settings, they are at the epicenter of the medication usage process. Therefore, it is prudent to think about how they perceive generic medications. Physicians still express concerns regarding the general reliability and quality of generic pharmaceuticals as well as generic substitution of specific drug categories, despite the fact that they accept generic substitution due to regulatory and economic pressures. Objectives of the study: - The objective of the study is to analyze and comprehend the inaccessibility, from supply side in terms of prescriptions by doctors, in using generic medicines in the country, being the largest exporter of generic drug. Research Methodology: - To assess this paradox, this paper will focus on the supply side constraints for this inaccessibility. A primary survey is carried out through a structured questionnaire circulated among the physicians who are the prescribers of all kinds of medicines. The questionnaire contained relevant questions related to the issues under the study. While convenience sampling was carried out to reach the physicians nearby, the physicians within this designated location were chosen at random in order to avoid biasedness. The sample was collected from Cuttack and Bhubaneswar, the twin cities of Odisha that is home to a wide range of medical facilities, from small clinics to multi-specialty hospitals, and thus regarded as the health hub for the entire state. Statistical measures and other techniques are used as per relevance to analyze the data using SPSS and AMOS software.